Field test and evaluation on crop dividers of sugarcane chopper harvester - Bai, Jing; Ma, Shaochun; Wang, Fenglei; Xing, Haonan; Ma, Jinzhi; Hu, Jiwei (International Journal of Agricultural and Biological Engineering, 2021)
In South China, the tropical weather and climate result in severe sugarcane lodging problems which greatly hinders sugarcane mechanical harvesting. The main function of the crop divider is to lift lodged canes and facilitate base-cut cane feeding. In this study, a series of field tests were conducted on crop dividers of Liugong 4GQ-180 sugarcane chopper harvester. The tests were designed to identify the relationships of the performance index (maximum lifting height of sugarcane) and the main influencing factors (machine forward speed, rotational speed of inside scrolls, and ground clearance of crop divider toes). The single factor test was conducted to determine optimum range of these test factors: the forward speed (FS) was 2.0-4.0 km/h, the rotational speed of inside scrolls (RS) was 100-140 r/min, and the toe ground clearance (GC) was 0-5 cm. The orthogonal test (three factors and three levels) was carried out to determine the optimal combination of operating parameters: FS was 2.0 km/h, RS was 115 r/min, and GC was 0 cm. In addition, the range analysis of orthogonal test results revealed that the order of each test factor affecting crop divider performance was RS, FS, GC. This study was expected to provide valuable references for the optimal operation of sugarcane harvester crop dividers. Keywords: sugarcane chopper harvester, parameter optimization, machine forward speed, rotational speed of scrolls, ground clearance, maximum lifting height, field test, evaluation, crop divider DOI: 10.25165/j.ijabe.20211401.5621 Citation: Bai J, Ma S C, Wang F L, Xing H N, Ma J Z, Hu J W. Field test and evaluation on crop dividers of sugarcane chopper harvester. Int J Agric & Biol Eng, 2021; 14(1): 118–122.